PENGARUH DISIPLIN KERJA, PENGEMBANGAN KARIR DAN PELATIHAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN (STUDI KASUS: BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KOTA SURAKARTA) - Dyah Ayu Puri Palupi; Tabita Ratih Sekar Arum (Universitas Bina Taruna Gorontalo, 2023)
This study aims to analyze the effect of work discipline, career development, and human resource training on the performance of BKPSDM Surakarta employees. The hypotheses proposed in this study are H1: suspected work discipline affects employee performance, H2: suspected career development affects employee performance, H3: suspected human resource training affects employee performance, and H4: suspected work discipline, career development, and human resource training simultaneously affect employee performance. The research method used is a quantitative research using surveys and interviews, which are intended to provide explanations. Survey research is research that takes a sample from a population and uses a questionnaire as the main collection tool. Sampling using the purposive sampling method where the technique of determining the sample is done with certain considerations or criteria. The study involved 35 employees as respondents. The data were analyzed using multiple linear regression models using the SPSS v25 application. The results of the data analysis show that the Tcount value of the Work Discipline variable is 1.702, the Career Development variable is 1.980, and Human Resource Training is 2.439. As for the ttable value of 1.697. From the results of this study, it can be concluded that work discipline, career development, and human resource training partially and simultaneously affect the performance of BKPSDM Surakarta employees.